2005
DOI: 10.1103/physreve.72.046123
|View full text |Cite
|
Sign up to set email alerts
|

1dexpansion fork-core percolation

Abstract: The physics of k-core percolation pertains to those systems whose constituents require a minimum number of k connections to each other in order to participate in any clustering phenomenon.Examples of such a phenomenon range from orientational ordering in solid ortho-para H 2 mixtures to the onset of rigidity in bar-joint networks to dynamical arrest in glass-forming liquids. Unlike ordinary (k = 1) and biconnected (k = 2) percolation, the mean field k ≥ 3-core percolation transition is both continuous and disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…as the susceptibility [20,[22][23][24], which scales as χ (p) = lim N→∞ χ (p,N) ∼ (p − p * ) −γ in a continuous transition.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…as the susceptibility [20,[22][23][24], which scales as χ (p) = lim N→∞ χ (p,N) ∼ (p − p * ) −γ in a continuous transition.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…(20) to the simulation data of p max (N ) as shown in Fig. 4(a), p * andν 4 are estimated as p * 0.400(2) andν 2.4 (1).…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, k = 3-core percolation may be very sensitive to loops. A 1/d expansion for k = 3core percolation demonstrated that the mixed nature of the transiton remained to order 1/d 3 [43]. Of course, the loops are controlled perturbatively in this 1/d expansion, which is not the case for the hyperbolic tessellation.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless these negative results leave the question open for the countless other lattices (either regular or random) in any dimension. Further-more a perturbative expansion around the large dimension limit of [19] suggested that both the MF transition and its hybrid character survives.…”
mentioning
confidence: 99%